Computer networks, the internet and next generation networks a protocol-based and architecture-based perspective - Hoang, Thi-Thanh-Mai (Europäische Hochschulschriften. Informatik, 2012)
"Most computer network books are described based on a top-down or button-up layer-based perspective - allowing readers to learn about concepts and protocols in one layer as a part of a complex system. At each layer, the books illustrated the mechanisms and protocols provided at this layer to its upper layer. Unlike other computer network books, this book additionally provides protocol-based and architecture-based perspective to study the computer networks, the Internet and Next Generation Networks. The book starts with a short introduction to the computer network and their design - covering the basic reference models, the multimedia networking, Next Generation Networking and Mobile Networking as well as network planning considerations. Fundamental techniques are described - covering mechanisms, protocols, architectures and services to control the traffic and ensure the QoS for data and multimedia applications. For each technique, the author formulates the problem statement and illustrates complete solution - including basic idea, concept, architecture, protocol behaviour, their advantages and disadvantages."--Publisher.